Basics of pathogenesis of liver fibrosis - Gutkowski, Krzysztof (European Journal of Clinical and Experimental Medicine, 2012)
Liver fibrosis is a complicated biochemical process in which damaged regions of the liver tissue are encapsulated by an extracellular matrix with scar formation. It develops in all patients with chronic liver injury at variable rates depending in part upon the cause of liver disease and in part upon the host factors. This process occurs earliest in regions where injury is most severe, particularly in chronic inflammatory liver diseases due to alcohol or viral infection. The development of fibrosis usually requires several months to years of ongoing injury. The exact point in which fibrosis becomes irreversible is unknown however, increasing evidence suggests that even advanced stages of fibrosis may be reversible. An understanding of the molecular mechanisms involved in fibrogenesis process has a number of clinical implications. One of the most important is development of therapeutic interventions designed to impede or reverse hepatic fibrosis. This review discusses the current mechanisms underlying liver fibrosis.